Mathematics teachers’ professional development and identity in a distance education setting - Ponte, João Pedro da (2011)
This paper discusses the influence of an in-service distance education course in the construction of mathematics teachers’ professional identity, especially regarding their views and practices of reflection and collaboration and their relation with information and communication technology. The course was based in open-learning pedagogy and focused on conducting exploratory and investigative work in the mathematics classroom. Evaluation results show that the perspectives and involvement of the participant teachers depend very much on their previous professional experience and relationship with the Internet. Teachers that use e-mail for collaborative work found this a very stimulating experience whereas those with less professional involvement had some difficulty in assuming the roles and values required for this kind of activity.